Pengaruh Model Pembelajaran Inkuiri Terhadap Berpikir Kritis Siswa Pada Materi Pertumbuhan - Eryuni Ramdhayani; Syafruddin Syafruddin; Lestari Dekayanti (Peneliti.net, 2023)
This study aims to determine the effect of the inquiry learning model on students' critical thinking on growth material. This research was conducted in class XII at SMAN 1 Moyo Hulu, academic year 2021/2022. This study uses a quantitative research approach. The type of research used in this research is quasi-experimental research (Quasi-Experimental). The design used in this research is this research uses experimental methods with the research design used is the pre-test and post-test which will later be analyzed using the independent sample t-test to determine the effect of the inquiry learning model on students' critical thinking in subjects growth material biology. Based on the results of the independent sample t-test, it was found that 0.000 <0.05 with Ha accepted and Ho rejected. It can be concluded that inquiry learning influences students' critical thinking on growth material.